Controlling molecular assembly in two dimensions: the concentration dependence of thermally induced 2D aggregation of molecules on a metal surface - Stöhr, Meike; Wahl, Markus; Galka, Christian; Riehm, Till; Jung, Thomas A.; Gade, Lutz H. (Angewandte Chemie. International edition, 2005)
Dilution principle in two dimensions: One building block yields three forms of aggregation on variation of the surface concentration of the molecular precursor (see picture; ML=monolayer coverage). Upon annealing at 300 °C, highly robust 2D aggregates are obtained on metal surfaces which lend themselves to the construction of hierarchic systems of higher complexity.
Gesehen am 16.12.2022